The Implementation Of Critical Educational Program In Improving The Knowledge And Skills For Women In Central Java - Moh. Yamin Darsyah; Padmaningrum Padmaningrum (CV The Journal Publishing, 2022)
Issues that will be researched are to know the success and the ability of trainees of critical educational programs in terms of awareness and independence. The formulation of the problem can be determined as follows: how the implementation of critical education in improving the knowledge and skills for women in Central Java. how the impact of the implementation of critical educational programs towards the awareness of women in Central Java Province. The implementation of critical education in improving the knowledge and skills for women in Central Java is by doing some teaching materials that suit the needs of the trainees, while the material is given on an ongoing basis and is based on the strategic issues that exist, then combined according to their needs, the material given such as workshop planning, assessment and organizing groups, gender training, gender awareness training, workshop planning of the establishment of women service center, training of social analysis, training of cadres/volunteers, advocacy training, training of community organizing, civic education training, management organizations training (community organizations), local resource management training, micro-enterprise management training, household economic management training, management training of Women Financial Institutions (LKP), and institutional strengthening of LKP.